Higher Education Faculty Perceptions of Open Textbook Adoption - Jung, Eulho; Bauer, Christine; Heaps, Allan (International Review of Research in Open and Distributed Learning, 2017)
The high cost of tuition and textbooks can have a negative impact on potential students from lower socioeconomic backgrounds. Open Educational Resources (OER) offers students a way to save educational costs while utilizing high-quality open textbooks. Up until now, there have been few studies focused on a specific provider of open textbooks. This study investigates open textbooks provided by OpenStax. Specifically, this study uses the COUP framework to examine: (1) cost reduction, (2) outcomes, (3) uses, and (4) the faculty perceptions of the quality of OpenStax textbooks. Additionally, we expanded the framework to address (5) the relationship between the perceived quality of the OpenStax textbook and the faculty perception of student performance, (6) the faculty’s intention to continue to adopt OpenStax textbooks, and (7) the perceived importance of accessibility to faculty who use OpenStax textbooks. Overall, the findings suggest that a significant amount of financial savings and a number of pedagogical shifts can be supported by the use of OpenStax textbooks.